The clinical outcomes of COVID‐19 in HIV‐positive patients: A systematic review of current evidence - SeyedAhmad SeyedAlinaghi; Amirali Karimi; Mehrzad MohsseniPour; Alireza Barzegary; Seyed Peyman Mirghaderi; Amirata Fakhfouri; Solmaz Saeidi; Armin Razi; Hengameh Mojdeganlou; Marcarious M. Tantuoyir; Amir Masoud Afsahi; Esmaeil Mehraeen; et al. (Immunity, Inflammation and Disease)
Abstract Introduction Patients with chronic underlying diseases are more susceptible to coronavirus disease 2019 (COVID‐19) complications. Recent studies showed people living with HIV (PLWH) are not at greater risk than the general population. Few studies have reviewed the impacts of COVID‐19 on PLWH. The purpose of this systematic review was to investigate the impact of COVID‐19 on patients infected with HIV. Methods We executed a systematic search using four databases of PubMed, Scopus, Science Direct, and Web of Science and screened the records in two steps based on their title/abstract and full text. This study follows the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) checklist to elevate the validity and reliability of its results. Results We reviewed 36 studies. The patients' age was above 20 years in all studies. In almost all studies, the inflammatory parameters were reported high. In most of the studies, all HIV patients completely recovered from the COVID 19 infection. Although CD4 count was not recorded in all studies, the minimum level was reported as 12 cells/µl. Conclusion Based on the current review, we concluded that HIV patients at advanced stages (3 or 4) of the disease, whose CD4 counts are low, may show less severe COVID‐19 infection symptoms. Similarly, Interference can reduce the severity of immune reactions and subsequent cytokine storms and consequently mitigate the symptoms. Therefore, in most of the studies, the majority of HIV patients showed no severe symptoms and completely recovered from COVID 19 infection.